113 Malignant Transformation of a Retroperitoneal Completely Isolated Enteric Duplication Cyst. (11th January 2018) - Gupta, Alia; Zhang, Ping; Amin, Mitual; Li, Wei
Abstract: Completely isolated enteric duplication cysts (CIDC) are extremely rare congenital malformations that are more common in younger male patients. They are predominantly intraabdominal and account for approximately one in 10, 000 live births. They have no connection to the gastrointestinal tract (GIT) and possess a dedicated vascular pedicle. They are uncommon variants of true duplication cysts, which themselves are characterized by the presence of gastrointestinal mucosal epithelial lining, attachment to the adjacent GIT, presence of smooth muscle in the wall, and sharing of blood supply with the native bowel. Malignant transformation is very infrequent. Henceforth, we describe an unusual case of retroperitoneal CIDC with transformation to mucinous cystadenocarcinoma in an elderly woman. A 64-year-old woman presented with complaints of abdominal pain, which was later diagnosed as a retroperitoneal non-communicating isolated duplication cyst. It was confused with renal cell carcinoma on imaging. Left-sided kidney, along with the adjacent cystic mass, was excised. Grossly, the complex cyst was separated from the kidney by a 1 mm fibroconnective tissue. On histology, the cyst wall had an enteric mucosal lining with presence of smooth muscle layers below the epithelium. The epithelial lining showed transformation to high-grade dysplasia and ultimately mucinous cystadenocarcinoma. The kidney showed no significant pathologic abnormalities. On immunohistochemical staining, the diagnosis was confirmed by expression of CDX2, CK7, CK20, MUC1, MUC6, and P504S, but was negative for MUC2, ER, and WT-1. This rare entity is not well-known but can be diagnosed and treated easily. It can have a high-risk of transformation to malignancy if left untreated, although it is unusual. Also, unlike true duplication cyst, it can be surgically resected without disturbing the adjacent bowel. Therefore, awareness of the lesion, with early and appropriate diagnosis, is essential for improved patient prognosis.